Serum lipopolysaccharide associated with new-onset atrial fibrillation in patients with non-small-cell lung cancer a retrospective observational study - Xu, Haifeng; Zhou, Jie; Ye, Fei; Gao, Yongzhuang (Frontiers in Surgery, 2024)
Lipopolysaccharide (LPS) is related to atrial fibrillation (AF). But so far, the relationship between LPS and new-onset AF (NOAF) in patients with lung cancer is unrevealed. This study was to investigate the association between LPS and NOAF in patients after lung cancer surgery. This was a single-center retrospective clinical observational study. Patients diagnosed with non-small-cell lung cancer (NSCLC) were enrolled. All patients receiving lung cancer surgery and at least 24h electrocardiogram (ECG) examination was recorded during the hospitalization. The incidence of NOAF in this study was 34/406 (8.4%). The univariate analysis showed that NOAF was associated with age, intraoperative blood transfusion (IBT), chronic obstructive pulmonary disorder (COPD), and LPS. After adjusting risk factors, it was found that age, IBT and LPS (OR 1.031；95% CI，1.001-1.042；p = 0.002) were still risk factors for NOAF. The area under curve (AUC) value was 0.709 for the LPS.When the LPS was added to the conventional model, the Net reclassification index (NRI) and integrated discrimination index (IDI) were improved significantly. Elevated LPS is associated with an increased risk of NOAF in patients after lung cancer surgery.LPS contributed to the discrimination of the NOAF risk model and improved it markedly.